Drying of peach (Prunus persica) using the refracting window technique - Quispe Talla, Angel (2017)
The investigation is framed in the biometric measures the characterizations of the aguaymanto expended in the alley of Huaylas as well as its hygienization with ozonated water, and then standardized the chemical peeling with 2 percent of soda and temperatures of 80º and 85º with immersion times of 2 minutes.The peeled pulps of Aguaymanto were subjected to the syrups with sugar solutions and in solutions of bee honey of 35, 45.50 Brix, at temperatures of: 25 ° C, 30 ° C, 35 ° C and Immersion times: 150 min, 180 min, 210 min respectively, reaching a final humidity of 22 percent.The optimum parameters for Osmo dehydration of Aguaymanto in solutions of honey of Bee is using 50% of soluble solids at 35 ° C that in a period of 150 minutes reaches its balance, reason why it is possible to prolong the life of Aguaymanto by more of 30 days by the use of direct osmohydration without altering its shape or texture. The characteristics of sensorial quality that showed the products were of acceptable and of preference on the products traditionally offered in the market.The research carried out in the valley of Callejón de Huaylas in the provinces of Yungay and Carhuaz with peaches of the peach variety, sought other forms of transformation in the line of dehydrated products, using new technologies that allow energy saving as well producción con variables cuantificables sobreas maintenance of its nutritional qualities, functional organoleptic as is the dehydration in refracting window.The work used peaches of discarding taking advantage of its pulp usable arriving at the following conclusions arriving at the conclusions; the parameters of dehydration of the peach through the use of refractory window without using temperatures higher than 60 ° C report the following values: Mo: Initial solids moisture: 5,214 (mg H 2 O / mg ss) - Rc: Constant drying rate (Mg H 2 O) / (mm 2 x min) - Mc: Critical Humidity: 2.23 mg H2O / mg ss - Me: Equilibrium Humidity: 0.85 mg / mg ss. Values of the dehydration kinetics obtaining a drying rate of 0.011 (mg H 2 O) / (mm 2 x min), to maintain its characteristics, technological, nutritional, functional and sensorial.The optimum parameters for dewatering in a refractory window were 60 degrees Celsius in a time of 4 hours, the dimensions of the solid for dehydration through the refracting window were 40 mm long, 15 mm wide and 3 mm thick.The drying curves in the graph allowed to have a dehydrated peach of intermediate humidity with 40.43 percent of humidity, 59.57 percent of dry matter, 57.36 percent of sugar, acidity of 0.68 percent of malic acid, 2.47 percent of reducing sugars and a lower microbial load of 1.32 CFU / g. Discarding peaches were used without commercial value in quantities of 2 kilograms, 8 percent of 25 kilograms representing on average 36 units that dehydrated has a great commercial value.